Targeting deubiquitinase USP7-mediated stabilization of XPO1 contributes to the anti-myeloma effects of selinexor - Junying Wang; Mengping Chen; Jinxing Jiang; Yike Wan; Xin Li; Minyue Zhang; Fei Xiao; Lu Zhong; Hua Zhong; Zhaoyu Qin; Jian Hou (Journal of Translational Medicine)
Abstract Background Targeting exportin1 (XPO1) with Selinexor (SEL) is a promising therapeutic strategy for patients with multiple myeloma (MM). However, intrinsic and acquired drug resistance constitute great challenges. SEL has been reported to promote the degradation of XPO1 protein in tumor cells. Nevertheless, in myeloma, the precise mechanisms underlying SEL-induced XPO1 degradation and its impact on drug responsiveness remain largely undefined. Methods We assessed XPO1 protein and mRNA levels using western blotting and RT-qPCR. Cycloheximide (CHX) chase assays and degradation blockade assays were used to determine the pathway of XPO1 degradation induced by SEL. The sensitivity of MM cell lines to SEL was evaluated using CCK8-based cell viability assays and AV-PI staining-based cell apoptosis assays. The subcellular localization of the cargo protein RanBP1 was assessed via immunofluorescence staining. Immunoprecipitation coupled with mass spectrometry (IP-MS), bioinformatics analysis and ubiquitination assays, were employed to identify the molecular targets responsible for SEL-induced degradation of XPO1. shRNA-mediated knockdown assays and small molecule inhibitors of USP7 were utilized to disrupt the function of USP7. The role of USP7 in modulating SEL sensitivity was analyzed in MM cell lines, primary CD138+ cells, and xenograft mouse models. Results SEL promotes the degradation of XPO1 in MM cells through the ubiquitin–proteasome pathway. There is a positive correlation between XPO1 degradation and sensitivity to SEL in these cells. Inhibiting XPO1 degradation reduces the functional inhibitory effects of SEL on XPO1, as evidenced by decreased nuclear localization of the cargo protein RanBP1. USP7 stabilizes XPO1 in MM cells via its deubiquitinating activity. SEL accelerates the ubiquitination and subsequent degradation of XPO1 by disrupting the interaction between XPO1 and USP7. The expression of USP7 is negatively correlated with patient prognosis and the sensitivity of MM cells to SEL. Inactivating or knocking down USP7 significantly enhances the anti-myeloma effects of SEL both in vitro and in vivo. Conclusion In conclusion, our findings underscore the essential role of XPO1 degradation in the anti-myeloma efficacy of SEL and establish a research foundation for targeting USP7 to improve the effectiveness of SEL-based therapies in MM.